Why Does Women's Underrepresentation Transpire in the Leadership of Indonesian State Islamic Universities? - Abidin, Zainal; Ghani, Muhammad Faizal A.; Pabbajah, Mustaqim; Fatmawati, Erma (JURNAL AL-TANZIM, 2023)
Underrepresentation of women still occurs in the top-level management of higher education, including in State Islamic Higher Education (SIHE/PTKIN) in Indonesia, a country with the largest Muslim population in the world. This study aims to reveal the portrait of women's underrepresentation in the top-level management of SIHE, the determinant factors that cause the underrepresentation of women in the top-level management of SIHE, and the policies that need to be taken in response to the underrepresentation of women in top-level management of SIHE. A qualitative approach was chosen for this study by collecting data using interviews and document reviews. It objectively shows the inequality between women and men in top-level management. Men still dominate strategic positions such as rector, vice-rector, and dean. This inequity is caused by qualification barriers of female lecturers, patriarchal culture, and gender-biased religious understanding. This inequity has an impact on the slow realization of gender-responsive campuses. Thus, through the Ministry of Religious Affairs, the Government must make affirmative policies to accelerate women's representation at the management level of SIHE so that more women occupy the positions of rector, vice-rector, and dean.